Icarisid Ⅱ modulates mitochondrial dynamics for anti-HBV activity - Liu, Zhengyun; Yang, Haiyan; Wen, Juan; Xiao, Dongyan; Yu, Wan; Luo, Guo; Gong, Qihai; Wang, Huan (Frontiers in Pharmacology, 2025)
IntroductionTo investigate the potential anti-hepatitis B virus (HBV) activity of Icariside Ⅱ (ICS Ⅱ), and elucidate its underlying mitochondrial dynamics mechanisms.MethodsThe study employed in vivo and in vitro assays to evaluate anti-HBV effects of ICS Ⅱ. An HBV replicating mouse model was established through hydrodynamic injection of pAAV/HBV1.2, the impact of ICS Ⅱ on HBV replication and liver toxicity was assessed. In vitro cell-based assays used HBV-positive HepG2.2.15 cells. Cytotoxicity was determined with CCK-8 assay, while ELISA and qPCR were employed to measure HBsAg, HBeAg, and HBV DNA levels. The livers of ICS II-treated HBV-infected mice were taken for transcriptome sequencing to screen for different genes, and the results were verified by Western Blot. Mitochondrial morphology and dynamics were visualized using confocal imaging and transmission electron microscopy. Key protein expressions related to mitochondrial fission and fusion were analyzed via WB. Intracellular ROS generation was assessed using fluorescence staining.ResultsThe study found that ICS Ⅱ exhibited significant anti-HBV effects both in vivo and in vitro. The results of RNA-Seq indicated that ICS Ⅱ modulated the mRNA levels of Fisl, a protein associated with mitochondrial dynamics, during the anti-HBV response. It induced mitochondrial fragmentation and enhanced mitochondrial motility in HBV-positive cells. Notably, key proteins associated with mitochondrial fission and fusion demonstrated alterations favoring fission. Furthermore, ICS Ⅱ effectively reduced ROS production in HBV-positive cells.ConclusionICS Ⅱ exhibits significant anti-HBV potential through its regulation of mitochondrial dynamics and ROS production.